Supervisi Kepala Sekolah Dalam Proses Pembelajaran Pendidikan Agama Islam: SMP Negeri 1 Keritang Kabupaten Indragiri Hilir - Irjus Indrawan; Rania Muspa; Dea Sahida Ruhina; Kartika, Adelda (Jurnal Pelita Manajemen Pendidikan, 2024)
Abstract This research aims to examine the supervision of school principals in the Islamic Religious Education learning process at SMP Negeri 1 Keritang. This research approach uses descriptive qualitative research methods with the technique of determining research objects carried out purposively. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis technique uses a flowing data analysis model, which includes: data reduction, data presentation, and drawing conclusions. Based on the results of research data analysis, the conclusions obtained are: First: The principal's supervision in the Islamic Religious Education learning process at SMP Negeri 1 Keritang has been implemented, such as involving teachers in creating school programs, providing direction to teachers who are experiencing difficulties in teaching, making arrangements. orderly regarding teacher discipline and conducting school program assessments at the end of the semester. Second: Factors that influence the principal's supervision in the Islamic Religious Education learning process at SMP Negeri 1 Keritang, namely low teacher teaching motivation, lack of discipline, lack of developing teaching media, lack of learning innovations, teachers often arrive late, do not comply with the calendar education, the level of education does not match the requirements to become a teacher, teachers are less skilled in dealing with deficiencies in teaching, teachers look for side jobs because the salary is inadequate, and schools do not care about teachers' health. Third: The principal's efforts to improve supervision in the Islamic Religious Education learning process at SMP Negeri 1 Keritang are by always discussing various activity problems at school, looking for solutions with teachers and the school committee, planning teaching and learning activities, involving teachers in various activities teaching, as well as looking for breakthroughs to obtain budget funds. Keywords: Supervision, Principal, Learning, Islamic Religious Education.